Decrease of Hepatitis C Burden in Patients With Transfusion Dependent Beta Thalassemia Major, Thalassemia Research Center, 1995 - 2014 - Mehrnoush Kosaryan; Aily Aliasgharian (Mazandaran University of Medical Sciences, 2015)
Background: Chronic hepatitis C infection used to be one of the most important burdens on patients with transfusion-dependent beta thalassemia major (TDTM). Chronic active hepatitis reduces quality of life, and liver cirrhosis and cancer shorten life expectancy in many cases. Objectives: We compared the characteristics of our patients at the Thalassemia Research Center (TRC) regarding hepatitis C infection at two time points. Patients and Methods: A review was conducted in a cohort of 390 TDTM patients with a history of at least one blood transfusion in 2014. Type of treatment protocol for hepatitis C virus (HCV) and the number of courses were defined. Descriptive statistics were performed using SPSS software (V16). Results: Screening for HCV started in 1995 at the TRC. Seventy-seven (15%) patients were antibody-positive in 1995. Tests for virus detection were not available at the time. Patients have been examined using serum AST, ALT, bilirubin, PT, PTT, and liver biopsy, and 45 were treated using alpha interferon alone. A second liver biopsy was performed at the end of treatment for 21 patients, and a blinded pathologist compared the histology according to the Knodell score. According to normalization of liver enzymes, the treatment was successful (McNemar test, P < 0.02). Based on the Knodell score, 54%, 31%, and 11% had complete, partial, and no response, respectively. A quantitative test for viremia became available thereafter. Thirteen patients who were resistant to alpha interferon have been treated using "Pegasys"™ ± ribavirin. Ten patients responded; however, three have been resistant and are still viremic. Twenty-seven patients received no treatment. Twenty-two (81.4%) had negative PCR tests. Five viremic patients refused treatment. A second screening test for HCV antibody was introduced in 2001, and, since then, annual screening for HCV antibody has been performed for all patients. No new case has been found since 2001. During the follow-up period, two deaths have been recorded in the cohort; none was a direct consequence of liver disease. Both patients had negative PCR tests for viremia. In 2014, there were 72 patients (52% men) with positive antibody tests, with a mean age of 30.5 ± 5.7 years. They mean age at the first blood transfusion was 2.8 ± 2.5 years. At the time of publishing, 15 patients (3.8%; 95% confidence interval 2 - 5.6) had viremia. Five patients had documented liver cirrhosis. Conclusions: The prevalence of hepatitis C virus has decreased dramatically owing to primary prevention (donor blood screening and discarding infected blood) and antiviral treatment of affected patients. Better clinical management with iron chelating agents and supportive therapy for cirrhotic patients is also in place.